2017
DOI: 10.1377/hlthaff.2017.0689
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Quadrupled Among Opioid-Driven Hospitalizations, Notably Within Lower-Income And Disabled White Populations

Abstract: Hospitals play an important role in caring for patients in the current opioid crisis, but data on the outcomes and composition of opioid-driven hospitalizations in the United States have been lacking. Nationally representative all-payer data for the period 1993–2014 from the National Inpatient Sample were used to compare the mortality rates and composition of hospitalizations with opioid-related primary diagnoses and those of hospitalizations for other drugs and for all other causes. Mortality among opioid-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 27 publications
4
72
0
1
Order By: Relevance
“…This racial/ethnic and income gradient is consistent with prior research describing the unique concentration of the opioid epidemic in low-income and majority-white areas. 2,3 …”
Section: Resultsmentioning
confidence: 99%
“…This racial/ethnic and income gradient is consistent with prior research describing the unique concentration of the opioid epidemic in low-income and majority-white areas. 2,3 …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that adverse labor market conditions may contribute to higher disability rates (Black et al, 2002;Autor and Duggan, 2003;Erceg and Levin, 2014;Hall, 2015). Similarly, as chronic diagnosed pain is by itself grounds for disability, the direction of causation between opioid use and disability may run in either direction (GAO, 2011;Morden et al, 2014;Meara et al, 2016;Buchmueller and Carey, 2017;Song, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A previous CDC analysis of drug overdose deaths (prescription opioids and heroin were the main causes) using the 2013 and 2014 national data found that age-adjusted mortality rates for Whites, Blacks and Hispanics were 19, 10.5 and 6.7 per 100,000 [3]. In a study of OUD-hospitalization mortality, Whites, ages 50-64, Medicare beneficiaries with disabilities, and residents of lower-income areas were noted to have higher odds of opioid/heroin poisoning [26]. These studies provide one potential reason for higher mortality in Whites and are consistent with our observation of an independent association of White race with higher mortality during OUD-hospitalization, adjusted for age, sex, insurance, income, comorbidity, hospital region (rural/urban) and teaching status, location or bed size.…”
Section: Discussionmentioning
confidence: 99%